221k views
4 votes
Given that f(x)=x^(2)-14 and g(x)=9-x, find (f-g)(6), if it exists.

2 Answers

3 votes

f(x)=x^2-14

g(x)=9-x

Find g(6)


\\ \sf\longmapsto g(6)=9-6=3

Now


\\ \sf\longmapsto (f-g)(x)=f(g(x))


\\ \sf\longmapsto f(g(6))


\\ \sf\longmapsto f(3)


\\ \sf\longmapsto 3^2-14


\\ \sf\longmapsto 9-14


\\ \sf\longmapsto -5

User Goodword
by
5.4k points
3 votes

Answer:

  • -5

Explanation:

Given:

  • f(x) = x² - 14 and g(x) = 9 - x

Find (f-g)(6):

  • g(6) = 9 - 6 = 3
  • (f-g)(6) = f(g(6)) = f(3) = 3² - 14 = 9 - 14 = -5
User Pankaj Rupapara
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.